Analysis of Prospects of Refilling Mineral Water Business in The City Palangka Raya - Febri Humisar Ompusunggu; Andrie Elia Embang; Sabirin Sabirin (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2019)
This study aims to determine and analyze: 1) The factors that influence consumer demand forrefill drinking water in Palangka Raya City; 2) The effect of per capita income, average price andpopulation on the demand for water in Palangka Raya City; and 3) Growing demand for refilldrinking water in the City of Palangka Raya. The research methods in this thesis are descriptivestatistical analysis, multiple linear regression, and linear trend analysis. The independentvariables in this study are family income, water prices, and the number of family members whilethe dependent variable is the business prospects of mineral water refill. The population in thisstudy is the number of households that consume water from mineral water refill depots in theCity of Palangka Raya. The sample in this study were 40 respondents in the City of PalangkaRaya based on the theory of sampling and sample size by Uma Sekaran in multivariate research.The type of data used is primary data and secondary data. The results of this study indicate that:1) Factors affecting the demand for mineral water based on primary data are consumer income,water prices, and the number of family members; 2) Simultaneously (simultaneously) there is a significant relationship between consumer income, the average price of water, and the number offamily members to the demand for mineral water in Palangka Raya City; and 3) There is agrowth in demand for mineral water based on per capita income, the average price of brandedwater, and the number of residents in the City of Palangka Raya